2015
DOI: 10.1371/journal.pone.0128527
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Nucleotide Polymorphism in an Endo-1,4-β-Glucanase Gene Controls Seed Coat Permeability in Soybean

Abstract: Physical dormancy, a structural feature of the seed coat known as hard seededness, is an important characteristic for adaptation of plants against unstable and unpredictable environments. To dissect the molecular basis of qHS1, a quantitative trait locus for hard seededness in soybean (Glycine max (L) Merr.), we developed a near-isogenic line (NIL) of a permeable (soft-seeded) cultivar, Tachinagaha, containing a hard-seed allele from wild soybean (G. soja) introduced by successive backcrossings. The hard-seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 49 publications
4
64
0
2
Order By: Relevance
“…Recently, a quantitative trait locus encoding calcineurin-like protein, GmHs1-1, was isolated by map-based cloning and reported to contribute to hardseededness in soybean with unknown mechanism (20). At the same time, an endo-1,4-β-glucanase gene, qHS1, was cloned by fine mapping and reported to be responsible for the formation of minute cracks by changing cell wall structure (19). Interestingly, these two genes are adjacent to each other in the physical map.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a quantitative trait locus encoding calcineurin-like protein, GmHs1-1, was isolated by map-based cloning and reported to contribute to hardseededness in soybean with unknown mechanism (20). At the same time, an endo-1,4-β-glucanase gene, qHS1, was cloned by fine mapping and reported to be responsible for the formation of minute cracks by changing cell wall structure (19). Interestingly, these two genes are adjacent to each other in the physical map.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, seed hardness has been identified as a quantitative trait in soybean (17,18). With quantitative trait locus marker analysis, two single nucleotide polymorphism alleles were found to be associated with a seed coat permeability trait in various soybean cultivars (19,20). The mechanisms that change seed coat properties remain unknown.…”
mentioning
confidence: 99%
“…Although its cellular functions are unknown, a large percentage of soybean landraces carry a SNP that causes an amino acid substitution and show low polymorphism in the c. 160 kb genomic region surrounding GmHs1-1, indicating a possible signature of artificial selection during soybean domestication. Water permeability is controlled by several additional QTLs (Liu et al, 2007;Orazaly et al, 2015); of those, the causal gene of the qHS1 locus is shown to encode an endo-1,4-b-glucanase that controls the amount of b-1,4-glucans in the outer layer of palisade cells of the seed coat on the dorsal side of seeds, a point of water entrance (Jang et al, 2015). Some of the seed permeability QTLs underlie seed coat cracking (Nakamura et al, 2003).…”
Section: Seed Hardnessmentioning
confidence: 99%
“…At molecular level, a single nucleotide polymorphism (SNP) has been reported to convert the impermeable wild type seeds to permeable one. A base substitution (T→G; Isoleucine→Serine) in Endo-1,4-β-Glucanase gene led to accumulation of β-1,4glucan derivatives such as xyloglucan which resulted in impermeability of seed coat in soybean (Jang et al 2015). Sun et al (2015) also indicated involvement of similar mechanism in seed coat permeability in soybean.…”
Section: Viability Versus Seed Coat Permeabilitymentioning
confidence: 99%